2018
DOI: 10.1002/advs.201700614
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Phase Junction Electron Transport Layer Boosts Efficiency of Planar Perovskite Solar Cells

Abstract: In the planar perovskite solar cells (PSCs), the electron transport layer (ETL) plays a critical role in electron extraction and transport. Widely utilized TiO2 ETLs suffer from the low conductivity and high surface defect density. To address these problems, for the first time, two types of ETLs based on TiO2 phase junction are designed and fabricated distributed in the opposite space, namely anatase/rutile and rutile/anatase. The champion efficiency of PSCs based on phase junction ETL is over 15%, which is mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 32 publications
(81 reference statements)
0
40
0
Order By: Relevance
“…Numerous research outcomes have demonstrated that the energy band alignment and interfacial charge recombination between the ETL and perovskite layer exert a significant impact on the device performance. [ 4–7 ] Therefore, it is pre‐requisite to develop an ETL with tailored morphology, optoelectronic properties, and compatible band alignment with perovskite, in order to fabricate high performance PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research outcomes have demonstrated that the energy band alignment and interfacial charge recombination between the ETL and perovskite layer exert a significant impact on the device performance. [ 4–7 ] Therefore, it is pre‐requisite to develop an ETL with tailored morphology, optoelectronic properties, and compatible band alignment with perovskite, in order to fabricate high performance PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…To find the influences of the perovskite and ETL on the charge dynamics in the perovskite solar cells, electrochemical impedance spectroscopy (EIS) was measured, and the results are summarized in Figure S16 (Supporting Information). All EIS curves contain two circular arcs, which can be fitted as the charge transport resistance ( R ct ) at the high‐frequency region and the charge recombination resistance ( R rec ) at the low‐frequency region 42–44. All fitted parameters are summarized in Table S4 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We can fit the charge transport resistance ( R ct ) of P‐FTO/perovskite interface from the high‐frequency circular arcs which reflects the carrier extraction ability of ETL. The carrier recombination resistance ( R rec ) can be extracted from the low‐frequency circular arcs which is inversely proportional to interface recombination . The series resistance ( R s ), R rec , and R ct are shown in the inset table.…”
Section: Resultsmentioning
confidence: 99%